Стекло в римской поэзии - Бударагина, Ольга Владимировна (Philologia Classica, 2007)
The article touches upon metaphorical usage of vitrum and vitreus in the Roman poetry of I century B. C. —IV century A.D.After commenting on different etymologies of the word vitrum, the author discusses various characteristics of glass found in poetical texts: its aquamarine colour, transparency, glitter, and brittleness. It is stated that Horace was the only Roman poet to mention all of them. At the same time, Claudian who makes use of vitreus more frequently than any of his predecessors pays attention only to the bluish colour of glass and thus pays tribute to the meaning, which is likely to be the original one. The author observes that starting with the so-called Silver Age poetry the adjective vitreus gradually replaces the noun. The article puts forward a criterion that might help to draw a distinction between the meanings of vitreus «transparent» and «aquamarine»: when the epithet is related to the seа, vitreus would rather mean colour; when it deals with a spring or a stream, the adjective apparently points out transparency and the lack of colour.